Penerapan Model Problem Based Learning (PBL) dalam Pembelajaran Matematika di UPT SDN 067952 - Simatupang, Wulan Purnama Sari; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This article aims to discuss the application of the problem based learning (PBL) model in mathematics learning at UPT SDN 067952. Mathematics learning is a mental exercise that involves understanding concepts, connections, and symbols before applying them to actual situations. Understanding ideas, using them to solve problems, and developing a mindset that appreciates the value of mathematics in everyday life are the goals of this mathematics education. In fact, there are still many who are relieved that learning mathematics is a student subject that is relatively the most challenging to learn and less interesting for students when they are in elementary school. This is because learning mathematics can be boring because of the use of models, techniques, and teaching materials. Therefore, the application of learning models is important, and one of these learning models is the Problem Based Learning (PBL) paradigm.